Madrasah di Era Peradaban Modern - Na’im, Zaedun (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
As an Islamic educational institution in Indonesia, madrasah emerged and developed along with the entry and development of Islam in Indonesia. Along with the development of the Indonesian nation, madrasas have experienced developments, both from the level and from the type since the sultanate, colonialism and independence. In this study the authors use qualitative research with a library study approach or library research and are descriptive in nature where the writer tries to explore how the position and the development of madrasah in the era of modern civilization. The results of this study, that madrasah as Islamic educational institutions function to connect the old system with the new system by maintaining old values ​​that are still good that can still be maintained and take something new in science, technology and economics that are beneficial to the lives of Muslims. With the emergence of several forms or models of madrasah developed by the Ministry of Religion shows that there is a desire for the development and reform of madrashs in following and meeting the needs and demands of development in this modern era, but does not erase the inherent tradition of madrasah.